The Role of Information Technology in Driving Innovation and Entrepreneurial Business Growth - Sutrisno Sutrisno; Arlis Dewi Kuraesin; Siminto Siminto; Irawansyah Irawansyah; Abu Muna Almaududi Ausat (Jurnal Minfo Polgan, 2023)
In the era of globalisation and rapid advances in information technology, the role of IT in driving innovation and growth of entrepreneurial businesses has become increasingly important. In this research, an in-depth analysis of the role of information technology in driving innovation and growth of entrepreneurial businesses will be conducted. This research will involve collecting secondary data from various sources. The focus of this study is primarily qualitative. Methods for gathering data include paying close attention to detail while seeing and recording data, and then using analytical techniques like data reduction, visualization, and inference to draw conclusions. The results of this study conclude that IT has a very important role in driving innovation and growth of entrepreneurial businesses. In today's digital era, entrepreneurs need to utilise IT effectively to accelerate product development, improve operational efficiency, expand market reach, drive business innovation, and enhance customer experience.